A Strengths Based Examination of the Educational Lives of Alaska Native Alumni of the University of Alaska Anchorage - Diane Erickson (Adult Education Research Conference, 2006)
This paper outlines a study currently underway to explore the pre-K through postsecondary educational lives of first-generation college, Alaska Native graduates of the University of Alaska Anchorage between the years of 1975 to 2005.
Keywords: Academic success; Alaska Native students